LOCAL COSMETICS MARKETING STRATEGY BASED ON DIGITIZATION TO BOOST SALES - Silvia Ekasari (CV. Adiba Aisha Amira, 2025)
In today's digital age, local cosmetics marketing strategies face challenges as well as opportunities. The research aims to develop digitization-based marketing strategies to increase sales of local cosmetic products. This research uses a qualitative approach to the study of literature. The findings show that digital marketing, through the use of social media, search engine optimization (SEO), and content marketing, plays a major role in increasing brand awareness and product sales. Other strategies such as influencer marketing, email campaigns, and affiliate marketing also proved effective in attracting and retaining consumers. Furthermore, personalization and unique customer experiences are key to creating added value for local cosmetic products in a competitive market. The research concluded that integrating comprehensive digital marketing strategies, coupled with an in-depth understanding of consumer preferences and market trends, can significantly boost sales of local cosmetic products.